Electrochemical Structural Stability of Au-Modified Pt Nanoparticles Prepared by Arc-Plasma Deposition. (14th September 2015) - Takahashi, Shuntaro; Chiba, HIroshi; Todoroki, Naoto; Wadayama, Toshimasa
Abstract : The electrochemical structural stability of Au-modified Pt nanoparticles (Au x /Pt100 NPs, where x is the atomic ratio of Au) was investigated. Au x /Pt100 samples were fabricated on a highly oriented pyrolytic graphite substrate at 773 K through sequential arc plasma depositions of Pt followed by Au. In cyclic voltammograms of Au x /Pt100, characteristic currents correlated to the corner and edge sites of the Pt NPs (0.13 V vs. RHE) decreased with increasing x . Electro-chemical surface area decay, observed after applying potential cycling between 0.6 and 1.0 V, clearly show that surface modification of the Pt NPs with appropriate amounts of Au atoms located at the corner and edge sites improved the structural stability of the Pt NPs.